RELIGION AND POLITICS IN ASIA - Chief Editor (Journal of Dharma, 2000)
The first and second numbers of Journal of Dharma were published together in 1975. Likewise now we are bringing out the 99 th and 100th numbers together. The theme of these two numbers is "Religion and Politics in Asia Today". Most of the articles of this issue are papers presented at the International Seminar on the same theme, which we organized here on the occasion of the Silver Jubilee celebrations of Journal of Dharma on 30 June to 03 July 2000. Some of the papers of the Seminar were published in the last issue.